1988
DOI: 10.1152/ajpcell.1988.255.1.c123
|View full text |Cite
|
Sign up to set email alerts
|

Liver and heart mitochondria in rats submitted to chronic hypobaric hypoxia

Abstract: Mitochondrial mass was determined in the heart and liver of rats submitted to 4,400 m (simulated altitude) for 9 mo and their controls at sea level. This was done 1) by evaluation of isolated mitochondrial protein per gram of tissue, 2) by evaluation of the ratio between cytochrome oxidase activity in tissue homogenate and in isolated mitochondria, and 3) by evaluation of mitochondrial numerical and volume density in fixed tissues analyzed by electron microscopy. An increase in mitochondrial mass and a more ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(52 citation statements)
references
References 9 publications
2
49
1
Order By: Relevance
“…The mechanisms behind this reduction in Complex V activity are not known, but in preconditioning models it has been proposed that Complex V is directly inhibited either through the binding of the inhibitory factor (Vander Heide et al, 1996) or through S-nitrosylation (Sun et al, 2007). These results are in contrast to the results observed in hypobaric hypoxia-exposed rats, where mitochondrial properties were not changed, but mitochondrial density increased (Costa et al, 1988); however, the present study used complete anoxia versus hypoxia, therefore it is not surprising that the results differ. Whatever the mechanism is for a reduction in Complex V activity, its beneficial effects on the anoxic cell are clear.…”
Section: Complex V Activity Is Reduced By Long-term Anoxia Exposure Imentioning
confidence: 81%
“…The mechanisms behind this reduction in Complex V activity are not known, but in preconditioning models it has been proposed that Complex V is directly inhibited either through the binding of the inhibitory factor (Vander Heide et al, 1996) or through S-nitrosylation (Sun et al, 2007). These results are in contrast to the results observed in hypobaric hypoxia-exposed rats, where mitochondrial properties were not changed, but mitochondrial density increased (Costa et al, 1988); however, the present study used complete anoxia versus hypoxia, therefore it is not surprising that the results differ. Whatever the mechanism is for a reduction in Complex V activity, its beneficial effects on the anoxic cell are clear.…”
Section: Complex V Activity Is Reduced By Long-term Anoxia Exposure Imentioning
confidence: 81%
“…For the first category of studies, research has shown that there is either no change or a decrease in aerobic indicators of the heart and liver (Kayar and Banchero, 1987;Costa et al, 1988;Lewis et al, 1999;Kennedy et al, 2001). For studies of the second type, CS (Hochachka et al, 1982) and LDH activities of the heart were increased (Vergnes, 1971;Penney, 1974;Barrie and Harris, 1976;Ohtsuka and Gilbert, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…When scaled for RMR, seal liver VV(mt) was even greater (6.6× and 2.3×) than in rat and dog liver, respectively. As with the seal heart, we hypothesize that this increase in VV(mt) decreases the intracellular distance for oxygen diffusion and effectively increases diffusive conductance to maintain aerobic metabolism and organ function during periods of hypoxia while diving (Costa et al, 1988). Based on the hepatic clearance of indocyanine green (ICG) from the blood during voluntary dives, Davis et al (1983) showed that hepatic function was maintained in subadult Weddell seals during voluntary dives, even though hepatic arterial and portal blood flow were reduced as a result of the dive response.…”
Section: Interspecies Comparison Of the Livermentioning
confidence: 99%
“…As shown in in vitro and in vivo experiments, hypobaric pressure increases cellular oxidative stress and to promote hypoxia suggests that especially impairs function in mitochondria (Costa et al, 1988). As a result of this lipids, proteins and DNA damaged and irreversible damage occurs for cells frequently (Magalhaes et al, 2005).…”
Section: Discussionmentioning
confidence: 98%